Preliminary data concerning methodology of assessment of serum autoantibodies not included into CTS-s diagnostic criteria - Ząbek, Jakub; Palacz, Agnieszka; Krzewska, Iwona; Pyka, Joanna; Maśliński, Sławomir (Reumatologia/Rheumatology, 2006)
Authors are presenting preliminary data introducing a new way of complex analysis of the sera (ANA-positive but without estimated certain specificity), using for the neutralization and removing of “masking” (competing) antibodies (in the test ANA-Hep-2) a full bovine and spleen soluble protein extracts/called ENA, followed by further analysis of the antibody specificities present in neutralized sera by specific ELISA or Western-blott tests dependently on the basic pattern of ANA in the serum.